A SIGNIFICANT STRUCTURE REVIEW: DEEP POOLS AND FISH SPAWNING HABITAT IN FISHERIES MANAGEMENT - Sulie Ak Slat; Nazirah Mohamad Abdullah; Muhammad Hafiz Mod Yatim (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The sustainability of fisheries is intricately linked to the conservation of critical habitats, particularly deep pools that serve as vital fish spawning grounds. This systematic literature review aims to explore the significance of deep pools in the reproductive success and management of fish populations. The study identifies critical challenges in fisheries management, including habitat loss, environmental changes, and the need for targeted conservation efforts. To address these challenges, a comprehensive search and analysis of peer-reviewed articles from databases such as Scopus and Web of Science was conducted, focusing on research published between 2022 and 2024. The methodology followed PRISMA guidelines to ensure a rigorous selection process, resulting in 40 high-quality studies being included in the final review. The findings were divided into three themes: (1) fisheries management and conservation, (2) environmental impact on fisheries, and (3) methodological approaches in fisheries research. The findings highlight the crucial role of deep pools in supporting fish spawning, with evidence showing that these habitats contribute significantly to the maintenance and enhancement of fish stocks. Results indicate that well-managed deep pools can lead to an increase in fish population densities, underscoring their importance in fisheries management. However, the review also needs to identify gaps in the current understanding of the complex interactions between fish species and their spawning habitats. The conclusion emphasizes the necessity for integrated management strategies that prioritize the protection of deep pools to ensure the long-term sustainability of global fisheries.